DONGENG INDONESIA DAN DONGENG JEPANG : KOMPARASI UNSUR BUDAYA - Rahmah, Yuliani (Vocational College of Diponegoro University, 2017)
The background of this paper is based on the author's interest in folklore, especially fairy tales. By reading and studying the tales indirectly enrich the treasures of our knowledge, both knowledge related to the variety of ancient languages, as well as knowledge related to the original culture of other country . By reading a variety of the fairy tales, authors often find the tales in one country that has similarities with the tales of other countries. One of that tales is Indonesia fairy tale and Japanese fairy tale.From the two texts containing Indonesian tales and the Japanese tales, which is used as research data, the results of research show that some parts of that fairy tales have the same cultural background . However, nevertheless, from the differences , it can be concluded that Indonesian tales and Japanese tales do not affect each other. It can be seen from the characteristics of each fairy tale which is a picture of the life of the community where the fairy tale was born.